Long-term outcome in patients after treatment for Cushing’s disease in childhood - Pasternak-Pietrzak, Katarzyna (PLoS One, 2019)
INTRODUCTION: Cushing’s disease (CD) is a rare cause of hypercortisolemia presenting a major diagnostic and therapeutic challenge. Data on pituitary function in long-term follow-up after CD treatment in childhood is limited. AIM: Long-term assessment of patients of the Children’s Memorial Health Institute (CMHI) after CD treatment in childhood. MATERIALS AND METHODS: Retrospective analysis of 29 CD patients, mean age at the time of diagnosis 13.46 yrs. The long-term follow-up (FU) was done by: 1) obtaining the data from a patient’s questionnaire (75% of adult patients); 2) using the data from the last clinic visit for patients who did not respond to the questionnaire and for current CMHI patients. The average long-term FU from transsphenoidal pituitary surgery (TSS) was 10.23 yrs. RESULTS: At the latest FU: 18 patients (62%) had long-term disease remission after TSS1, 2 patients (6.9%) after TSS2, 1 patient (3.4%) after the post-TSS radiotherapy (XRT) cycle and 3 patients (10.3%) after bilateral adrenalectomy (BA). One patient (3.4%) died after TSS2 due to postoperative complications, 1 patient (3.4%) had persistent disease at latest FU, in 1 patient (3.4%) the long-term FU was not possible to perform. CD recurrence occurred in 4 out of 28 patients (14%) at an average time 3.6 yrs. from definitive treatment. One patient (3.4%) after BA was operated because of Nelson's syndrome. Two patients (6.9%) were suspected of relapse at latest assessment. At the time of the last evaluation, 17 patients (63%) were on levothyroxine therapy since definitive treatment, 16 patients (59%) were on hydrocortisone treatment, 10 patients (37%) were taking sex hormones replacement, 4 patients (15%)—antidiuretic hormone. CONCLUSIONS: Relatively large number of patients after CD treatment in childhood have hormonal pituitary deficits as well as mood and cognitive disorders. CD recurrence can occur even after a long time post effective treatment.